Kajian Tingkat Pendidikan Terhadap Kualitas Hidup Masyarakat - Bagas Ramadhana; Indah Meitasari (Jurnal Penelitian Pendidikan Geografi, 2023)
Education is a process of educating, developing and providing increased insight and knowledge in order to create individuals who have an important role in social life. Education is seen as a means to achieve a good level of quality of life. This study aims to describe the effect of education on quality of life. This research is a type of quantitative research using the WHOQOL-BREF scoring method to determine the level of quality of life. The results showed that the level of quality of life for the people of the Malaka Sari Village was very good. The level of education also influences the quality of life. There are other factors that are more influential but these factors are not explained in this study.